Sports tournament scheduling using genetic algorithm / Hafeezur Syakir Abdul Motok@Mohd Ridzuan - Abdul Motok@Mohd Ridzuan, Hafeezur Syakir (2020)
The organizer of sports events often fronting problems such as the incorrect allocation of matches as well as tough to create a good and reliable schedule. Most of the time, the difficulties created by the committee members was by the mistakes made by the human. The manual method is sluggish and tedious, not to mention costly when they have to process the data elsewhere. A highly constrained combinatorial problem, like the sports timetable, can be resolved by evolutionary methods. Thus, a schedule for the sports tournament is needed in order to delegate the matches in a tournament. The purpose of this research is to analysed the algorithm techniques and illustrate how the technique solves these problems. In this report, a Genetic Algorithm (GA) is applied for solving University sports timetabling problems. In genetic algorithm, there are steps include such as initialize population, selection, crossover, mutation and calculate fitness. These steps are repeat until a condition satisfied. The system uses the Rapid Application Development (RAD) methodology in system development and will be operate on a web-based platform. The phase in RAD such as planning requirements, user design, rapid construction and cutover is used during development. RAD highlights on user interaction and quick development of the system using prototypes. The functionality testing is conducted using Blackbox testing technique to test the functionality of the project.